2015
DOI: 10.1080/23808985.2015.11679179
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasiveness of Child-Targeted Endorsement Strategies: A Systematic Review

Abstract: Several European and U.S. reviews have established the link between food marketing and childhood obesity (EU Pledge, 2012; FTC, 2006;Persson, Soroko, Musicus & Lobstein, 2012), which has stimulated researchers to investigate the effects of the most prevalent child-targeted marketing technique: the use of endorsing characters. This systematic review of these studies (15 identified; participants age 3-12 years) focuses on three important questions: (a) Does a basic endorser effect exist?, (b) Is the strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
2
26
0
4
Order By: Relevance
“…27,28 These forms of embedded marketing, although scarcely studied in digital media, 29,30 likely have a profound impact on young people. 27,28 These forms of embedded marketing, although scarcely studied in digital media, 29,30 likely have a profound impact on young people.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 These forms of embedded marketing, although scarcely studied in digital media, 29,30 likely have a profound impact on young people. 27,28 These forms of embedded marketing, although scarcely studied in digital media, 29,30 likely have a profound impact on young people.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring the effect of celebrity endorsements of HFSS foods show that they can increase children's preferences, requests for, and intake of these products . One study looked at effects on children's (aged 8‐11 y) brand choice and intake by simultaneously offering children the endorsed brand and a perceived alternative brand and allowing them to choose the amount they consumed from each .…”
Section: Introductionmentioning
confidence: 99%
“…Second, another limitation is that our experimental design includes only two time points. Although the power of a toy has clearly been successful as a food marketing tactic [9, 10], there is still the possibility of a wear out effect over longer periods of time that future research could investigate. Third, based on prior research, the authors assumed the inclusion of a control condition, in which there was no toy offered, was unnecessary because in the absence of an incentive, a larger meal should always be more desirable than a smaller meal [12, 25, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, critics of food marketing suggested that, for children, toys are a key driver of fast food meal choice [8]. Relatedly, two recent systematic reviews found that character endorsers (e.g., McDonald’s Ronald McDonald) considerably increase children’s liking and preference for energy-dense foods [9, 10]. The effects of food marketing tactics on children, when used in this way, are especially worrisome because they likely establish and reinforce long-lasting food choice patterns [11].…”
Section: Introductionmentioning
confidence: 99%